The Influence of Audiovisual Media on Increasing Knowledge About Chronic Kidney Disease in Diabetes Mellitus Patients at RSUD dr. Soedomo Trenggalek Regency - Alfadhila, Azza Mi'raj; Ariastuti, Ni Luh Putu; Sari, Komang Ayu Kartika; Sawitri, Anak Agung Sagung (E-Jurnal Medika Udayana; Vol 14 No 01 (2025): E-Jurnal Medika Udayana, 2025)
Chronic kidney disease (CKD) represents a gradual decline in the capacity of the kidneys, manifested by a persistently reduced GFR below 60 mL/min/1.73 m² or demonstrably impaired kidney structure. It is crucial to prioritize the prevention of chronic kidney disease (CKD), particularly among individuals with predisposing factors. Diabetes mellitus (DM) stands out as a primary risk factor associated with CKD. Therefore, health promotion efforts are needed to prevent CKD in patients with DM. One such effort is through the use of audiovisual media, such as educational videos. This study aimed to determine the effect of audiovisual media on knowledge improvement of CKD in patients with DM. A quasi-experimental pre-experimental study with a one-group pretest-posttest design was conducted at RSUD dr. Soedomo Trenggalek Regency. A total of 36 patients with DM participated in this study. The results showed that the majority of respondents were female, aged 45-59 years, had a tertiary education level, had never received information about CKD before, and did not have a family history of CKD. The majority of respondents had an initial knowledge level of moderate. After the intervention, the majority of respondents had a final knowledge level of high. There was a significant effect of audiovisual media on the improvement of knowledge about chronic kidney disease (CKD) in patients with diabetes mellitus (DM) at RSUD dr. Soedomo Trenggalek Regency with a p value <0.001. The study concluded that there was a significant effect of audiovisual media on knowledge improvement of CKD in patients with DM at RSUD dr. Soedomo Trenggalek Regency. Keywords: chronic kidney disease (CKD), diabetes mellitus (DM), knowledge, audiovisual media